Cancer incidence in Gipuzkoa, Spain (1998-2002), and time trends from 1986 Incidencia del cáncer en Guipúzcoa (1998-2002) y tendencias desde 1986 - Nerea Larrañaga; Cristina Sarasqueta; M. Jesús Michelena (Elsevier, 2008)
Objectives: To determine the cancer incidence in Gipuzkoa (Spain) from 1998 to 2002 and describe time trends since 1986. Methods: The annual incidence of cancer in Gipuzkoa from 1998 to 2002 was estimated as a rate per 100,000 inhabitants. Incidence trends for the period 1986-2002 were studied for all cancers and for the main cancer sites using Poisson regression and Joinpoint regression for prostate tumours. Results: On average, one in 3 men and one in 5 women would probably be diagnosed with cancer at some time during their life (0-74 years). Among men, prostate surpassed lung as the most frequent cancer site. Among women, breast cancer represented approximately 30% of all cases of cancer (excluding non-melanoma skin cancers). There was an annual increase in the incidence of cancer of 1.5% (95% CI, 1.1-1.8) in men and 0.9% (95% CI, 0.5-1.3) in women. The incidence of prostate cancer in men increased over the study period, and especially between 1996 and 1999, with an annual increase of 34.7% (95% CI, 5.9-71.5). The incidence of lung cancer in women presented an annual increase of 5.2% (95% CI, 3.4-7.1). In contrast, the incidence of stomach cancer decreased during the study period. Conclusions: Cancer incidence in Gipuzkoa increased during the study period. This increase was particularly marked in lung cancer and skin melanoma, for which preventive strategies are fundamental. Objetivos: Conocer la incidencia de cáncer en Guipúzcoa entre 1998 y 2002, y su evolución desde 1986. Métodos: Se realizan estimaciones de incidencia anual del cáncer en el período 1998-2002, para Guipúzcoa, en tasas por 100.000 habitantes. Se analiza su evolución entre 1986 y 2002 en el conjunto de localizaciones y en las más frecuentes, mediante el modelo de regresión de Poisson y el modelo de regresión Joinpoint en tumores de próstata. Resultados: Uno de cada 3 varones y una de cada 5 mujeres de Guipúzcoa tienen la probabilidad de desarrollar cáncer a lo largo de su vida (rango, 0-74 años). En varones, el cáncer de próstata ocupa el primer lugar, seguido del cáncer de pulmón. En mujeres, el cáncer de mama representa cerca del 30% del total (excluido el de piel no melanoma). Se observa un incremento anual de incidencia en varones del 1,5% (intervalo de confianza [IC] del 95%, 1,1-1,8) y del 0,9% (IC del 95%, 0,5-1,3) en mujeres. Aumentan los tumores de próstata en varones, especialmente en el período 1996-1999 en un 34,7% anual (IC del 95%, 5,9-71,5), y el cáncer de pulmón en las mujeres en un 5,2% anual (IC del 95%, 3,4-7,1), mientras que los tumores de estómago descienden en el período de estudio Conclusiones: La incidencia de cáncer en Guipúzcoa aumenta en el período de estudio; destacan los tumores de pulmón y melanoma cutáneo, donde las estrategias preventivas desempeñan un papel primordial.